The Influence of Treatment of Inflammatory Arthritis During Pregnancy on the Long-Term Children’s Outcome - Nalli, Cecilia; Galli, Jessica; Lini, Daniele; Merlini, Angela; Piantoni, Silvia; Lazzaroni, Maria Grazia; Bitsadze, Victoria; Khizroeva, Jamilya; Zatti, Sonia; Andreoli, Laura; Fazzi, Elisa; Franceschini, Franco; et al. (Frontiers in Pharmacology, 2021)
The management of reproductive issues in women with inflammatory arthritis has greatly changed over decades. In the 1980-90s, women with refractory forms of arthritis were either not able to get pregnant or did choose not to get pregnant because of their disabling disease. Hence, the traditional belief that pregnancy can induce a remission of arthritis. The availability of biologic agents has allowed a good control of aggressive forms of arthritis. The main topic of discussion during preconception counselling is the use of drugs during pregnancy and breastfeeding. Physicians are now supported by international recommendations released by the European League Against Rheumatism and the American College of Rheumatology, but still they must face with cultural reluctance in accepting that a pregnant woman can assume medications. Patient-physician communication should be centered on the message that active maternal disease during pregnancy is detrimental to fetal health. Keeping maternal disease under control with drugs which are not harmful to the fetus is the best way to ensure the best possible outcome for both the mother and the baby. However, there might be concerns about the influence of the in utero exposure to medications on the newborn’s health conditions. Particularly, studies suggesting an increased risk of autism-spectrum-disorders in children born to women with rheumatoid arthritis has raised questions about neuropsychological impairment in the offspring of women with chronic arthritis. As a multidisciplinary group of rheumatologists and child neuropsychiatrists, we conducted a study on 16 women with chronic forms of arthritis whose diagnosis was determined before pregnancy and their 18 school-age children. The children underwent a complete neurological examination and validated tests/questionnaires. Behavioral aspects of somatization and anxiety/depression (internalizing problem) or an “adult profile” were found in nearly one third of children. Children at a high risk of neurodevelopmental problems were born to mothers with a longer history of arthritis and were breastfeed for less than 6 months of age or were not breastfeed at all. No association was found with other maternal characteristics such as autoantibody existence and disease activity during and after the pregnancy.